COMPARISON BETWEEN HB AND AGMA BEVEL GEAR STRENGTH CALCULATION STANDARD - LI XiangYu; LIU ShaoJun (Jixie qiangdu)
In this paper similarities and differences in Bearing Capacity Calculation of Aviation Bevel Gears（ HB / Z89.1 HB / Z89.4-85） and Rating the Pitting Resistance and Bending Strength of Generated Straight Bevel,Zerol Bevel and Spiral Bevel Gear Teeth（ ANSI / AGMA 2003-B97） were analyzed and compared.It was compared in scope,calculation principle,fundamental rating formulas,correction factors and calculation example such several aspects.The strength evaluation value was introduced to make it easy for comparison.The two standards have their own characteristics according to the research results.The former’s correction factors are considered more comprehensive,and the correction factors are subject to theoretical calculation; the latter’s calculation is simple and the correction factors are mainly based on experience formula and test data.The contact strength evaluation value of the former is larger than the latter,while the bending strength evaluation value is smaller.At last the conclusion is the former’s strength rating is more conservative.